European bloc imperialism - Canterbury, Dennis C. (Brill LeidenNL, 2010)
Seeks to establish the thesis about EU bloc imperialism, a phenomenon which was overlooked in the current literature. Attempts to provide an understanding of the modus operandi of present-day capitalism, under the rubic of new imperialisms in the twenty-first century.